Austrian Administrative Judiciary: The Reform and the New Paradigm - Radošević, Ratko S. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
In 2012, a major reform of the Austrian administrative judiciary has been completed. The reform is analysed in this paper after a brief presentation of the origin and development of the Austrian administrative judiciary and its classical, traditional features. The analysis includes the reasons and motivation for the reform, its course and the basic characteristics of the newly implemented system. At the end, it is concluded that the introduction of a two-level administrative judiciary, an administrative dispute of full jurisdiction and the abolition of appeals in administrative procedure in Austria have changed the paradigm of the legal protection of parties in administrative matters.
Keywords: judicial control of the administration, administrative dispute, administrative judiciary, Austrian administrative judiciary, reform of Austrian administrative judiciary